1988
DOI: 10.2307/2061327
|View full text |Cite
|
Sign up to set email alerts
|

Migration distances: An international comparison

Abstract: Comparing the level or amount of migration within different countries has been a longstanding problem because the local administrative areas commonly used as the basis for measuring migration vary greatly in size and significance within and between countries. Distance moved is a critical aspect of most concepts of migration, and measuring it would facilitate cross-national comparisons. Apparently only the United States, Great Britain, and Sweden have measured migration distances for the country as a whole, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 8 publications
2
35
0
1
Order By: Relevance
“…A journey of 25 miles at the most converts any native of Rutland into a "migrant," whilst a native of Yorkshire to place himself into the same position might have to travel as many as 95 miles." (Ravenstein, 1885:168) Since then a number of studies have shown that there is a strong deterrent of distance to migration flows (see e.g., Makower et al, 1938;1939;Hägerstrand, 1957;Olsson, 1965;Long et al, 1988a;1988b), and because migration is still almost exclusively defined by administrative borders, the problems identified over a century ago are equally valid today.…”
Section: Theory and Previous Researchmentioning
confidence: 99%
“…A journey of 25 miles at the most converts any native of Rutland into a "migrant," whilst a native of Yorkshire to place himself into the same position might have to travel as many as 95 miles." (Ravenstein, 1885:168) Since then a number of studies have shown that there is a strong deterrent of distance to migration flows (see e.g., Makower et al, 1938;1939;Hägerstrand, 1957;Olsson, 1965;Long et al, 1988a;1988b), and because migration is still almost exclusively defined by administrative borders, the problems identified over a century ago are equally valid today.…”
Section: Theory and Previous Researchmentioning
confidence: 99%
“…Long, Tucker, and Urton (1988) report the results of an analysis of the 1979 and 1980 Health Interview Surveys, which contain information on distance between current residence and the respondent's residence 3 yr earlier. For those respondents that moved only once during the 3-yr period (a group comprising approximately three-fourths of all who moved at least once during the 3-yr period), they find the median migration distance to be just over 10 km, or 6.2 miles.…”
Section: Four Myths About Mobility and Migration In The United Statesmentioning
confidence: 99%
“…Other studies have emphasized on comparisons between countries (Long 1991), migration distance (Long et al 1988), age structures (Castro and Rogers 1981), and other demographic characteristics (Long 1992). More recently, the 1999 United Nations World Monitoring Report (2000) Although most often people who move are attracted by better income opportunities, there other reasons why people relocate.…”
Section: Relocation In a Broader Perspective: Mobility In Other Contextsmentioning
confidence: 99%